2013
DOI: 10.4103/0301-4738.109519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intrastromal corneal ring segments for treatment of keratoconus with a mechanical implantation technique

Abstract: Purpose:To evaluate the clinical outcomes of intrastromal corneal ring segment (ICRS) implantation in patients with keratoconus using a mechanical implantation technique.Materials and Methods:Thirty eyes of 17 patients with keratoconus were enrolled. ICRSs (Keraring) were implanted after dissection of the tunnel using Tunc's specially designed dissector under suction. A complete ophthalmic examination was performed, including uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 28 publications
1
26
0
1
Order By: Relevance
“…Our results are in agreement with previous studies that reported significant corneal flattening changes after Keraring implantation 18,20,21…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in agreement with previous studies that reported significant corneal flattening changes after Keraring implantation 18,20,21…”
Section: Discussionsupporting
confidence: 94%
“…They reported a statistically significant reduction in the SE refractive error compared to that observed at the examination before implantation. Tunc et al18 reported a significant reduction in SE refractive error from −6.42±4.69 D preoperatively to −1.26±1.45 D ( P =0.001) at 1 year postoperatively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…74,75 An improvement in the corneal shape manifested as an improvement in inferior-superior corneal symmetry and centralization of the corneal apex has been reported. 67,[76][77][78] However, Alio et al, 79 in their retrospective study with longer follow-up (36-48 months), showed that ICRS implantation is incapable of maintaining the initial corneal flattening effect. In their series, the eyes implanted with ICRS showed a progressive increase in keratometry reading from 6 to 36 months.…”
Section: Momentioning
confidence: 93%
“…This decreases refractive errors and improves corneal surface regularity. Moreover, there is evidence to suggest that implanting an ICRS may delay the requirement for penetrating keratoplasty (7)(8)(9) . There are several commercially available ICRS that vary with regard to curvature, width, and zone of implantation (3) .…”
Section: Introductionmentioning
confidence: 99%